Digital Competences in Classical Music Teaching: From a Critical View to the Systematization of Digital Resources - Sanela Nikolić; Biljana Leković (INSAM)
The number and variety of online classical music digital resources require specific knowledge to independently search for, select and incorporate appropriate content into the teaching process, as these represent alternative teaching tools that go beyond the primary didactic materials. The basic assumption of this paper is that the digital competences of music teachers imply not only the mastery of tools – concrete digital resources – but also a specific theoretical knowledge of music encoding, storage and transposition informed by computer science as a prerequisite for developing a skill to use digital tools. The main contribution of this article is therefore to identify the key theoretical knowledge and digital resources that music teachers should understand to successfully develop and utilize their digital competences in the context of classical music teaching. The main principles and practices of music encoding, storage, and transposition are identified and explained regarding relevant academic studies. Based on an analysis and systematization, the open-access classical music digital resources are selected and classified, considering the most representative examples.